-3(3s-1)-3=-3(5s+6)-5

Simple and best practice solution for -3(3s-1)-3=-3(5s+6)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3s-1)-3=-3(5s+6)-5 equation:


Simplifying
-3(3s + -1) + -3 = -3(5s + 6) + -5

Reorder the terms:
-3(-1 + 3s) + -3 = -3(5s + 6) + -5
(-1 * -3 + 3s * -3) + -3 = -3(5s + 6) + -5
(3 + -9s) + -3 = -3(5s + 6) + -5

Reorder the terms:
3 + -3 + -9s = -3(5s + 6) + -5

Combine like terms: 3 + -3 = 0
0 + -9s = -3(5s + 6) + -5
-9s = -3(5s + 6) + -5

Reorder the terms:
-9s = -3(6 + 5s) + -5
-9s = (6 * -3 + 5s * -3) + -5
-9s = (-18 + -15s) + -5

Reorder the terms:
-9s = -18 + -5 + -15s

Combine like terms: -18 + -5 = -23
-9s = -23 + -15s

Solving
-9s = -23 + -15s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '15s' to each side of the equation.
-9s + 15s = -23 + -15s + 15s

Combine like terms: -9s + 15s = 6s
6s = -23 + -15s + 15s

Combine like terms: -15s + 15s = 0
6s = -23 + 0
6s = -23

Divide each side by '6'.
s = -3.833333333

Simplifying
s = -3.833333333

See similar equations:

| 5(c+7)=-42 | | 34+13+6a=100 | | 3(x+4)-6=-12 | | (x+20)+(x+10)+y+(y-40)=180 | | 2z+9.76-7z=-5.15 | | 12A+2+A-1= | | -2(t-1)+4t=6t-3 | | 16+346a=34 | | 7x^2+13x+1=3 | | 5x^3-9x^2-2x=0 | | -3(2s-6)-18=-3(9s+4)-3 | | -24=-8-6k+2k | | 95+-0.5y=180 | | 2x-5x+6.3= | | x^2-8x+16=22 | | -x+5x=-20 | | .4(c-8)+3=4 | | (8a^3-11)+(-5a-2)= | | 85+(-98)+21= | | 3i+-9-7i+21=6i+-16+-24 | | -10x-2x+3x= | | 2x-5(-3x+7)=-1 | | -20=-3x+8x | | 7r-9=-86 | | 4c+7-3c+8= | | -19=1-7p+8 | | 7r-2+5r=6r+6-4r | | 0.25+0.10(x-3)=1.1 | | 6y+3=4y-13 | | -4(23)= | | x+x+100=110 | | 100=8+9a |

Equations solver categories